Tough Love: Impact of High-Performance Work System on Employee Innovation Behavior - Zhu, Fuyun; Gao, Ying; Chen, Xiaotun (Frontiers in Psychology, 2022)
Based on social exchange theory, this paper discusses the impact of high-performance work system on employee innovation behavior, and constructs the mediating model of challenge stressors and the moderated mediation model, and explores the influence mechanism of high-performance work system on employee innovation behavior under the management mode of combining strictness and love formed by "strictness" under the effect of challenge stressors and "love" given by perceived organizational support. Through hierarchical regression analysis of 227 employees' survey data, the results show that there is a significant positive correlation between high performance work system and employee innovation behavior. Challenge stressors partially mediates the above relationship, and perceived organizational support positively moderates the mediating effect of challenge stressors between high performance work system and employee innovation behavior.